2015
DOI: 10.1302/0301-620x.97b6.34552
|View full text |Cite
|
Sign up to set email alerts
|

Porous titanium granules are better than autograft bone as a bone void filler in lateral tibial plateau fractures

Abstract: A total of 20 patients with a depressed fracture of the lateral tibial plateau (Schatzker II or III) who would undergo open reduction and internal fixation were randomised to have the metaphyseal void in the bone filled with either porous titanium granules or autograft bone. Radiographs were undertaken within one week, after six weeks, three months, six months, and after 12 months. The primary outcome measure was recurrent depression of the joint surface: a secondary outcome was the duration of surgery. The ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 24 publications
0
33
0
3
Order By: Relevance
“…A raft–screw plate is chosen. The articular surface is supported not only by a bone allograft but also by the raft screws.…”
Section: Discussionmentioning
confidence: 99%
“…A raft–screw plate is chosen. The articular surface is supported not only by a bone allograft but also by the raft screws.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium can perform as a bioactive material by modification of the surface characteristics obtaining micro-sized roughness. Jónsson randomized patients to titanium granules vs. autogenous graft and found superiority of titanium granules [112] . In addition to mechanical refinement, chemical surface treatment can also be utilized to inflect angiogenesis and trigger osteoblasts thereby accelerating healing.…”
Section: Metal Based Osteobiologicsmentioning
confidence: 99%
“…The final outcome is closely correlated with the accuracy of the underlying reduction achieved (Table 1). 18,33-43 …”
Section: Articular Impacted Fractures Of Lower Limbmentioning
confidence: 99%
“…56 Several studies have shown no significant difference in the clinical outcomes between cases treated with autografts or allografts and bone graft substitutes. 39,40,42,43 It should be mentioned that any concomitant injuries, such as meniscal tears or ligament ruptures, should be addressed simultaneously as they can negatively compromise the final outcome. Satisfactory results do not always correlate with the radiological appearance, possibly due to the function of the menisci that can bear weight and relieve pressure over the lateral compartment…”
Section: Clinical Outcomesmentioning
confidence: 99%